The Unknown Mindscapes: Gender Dysphoria and Romantic/ Sexuality Relationships in Autism Spectrum Disorder (ASD) - Catena, Silvestri Maria; Vitelli, Roberto; Rosaria Anna, Muscatello Maria; Carmela, Mento (Journal of Intellectual Disability - Diagnosis and Treatment, 2023)
Introduction: Higher percentages of gender dysphoria among autistic people has been recently observed. Previous studies showed that patients with autism spectrum disorders have difficulties in social communication and romantic relationships. Aim: In light of this, this manuscript aimed to study the quality of romantic relationship in autistic people and the possible role played by gender dysphoria. Methods: The search of the literature was conducted in this database: PubMed; we used these search terms: "autism spectrum disorder", "gender dysphoria", and "romantic relationship". We found a total of 74 citations. After excluding duplicates, 74 records were screened. 58 studies were excluded according to inclusion and exclusion criteria. A total of 16 studies has been finally assessed. Results: The findings of this work showed that autistic people have a difficulties in social and romantic relationships. A variety of difficulties in interpersonal and romantic relationships were detected, but to date, it is not clear how gender dysphoria could influence the possibility to initiating and maintaining romantic relationships as well as having a satisfying sexual life. Furthermore, different diagnostic instruments resulted in having been employed, and a general heterogeneity in the population under scrutiny was observed. Conclusions: Impaired social communication and interaction (SCI) and restricted, repetitive behavior (RRB) represent the two core symptom domains of ASD within the DSM-5. It is important to pay attention to these conditions, to manage the coming out about gender dysphoria in autistic people, and to develop strategies to help future social and romantic relationships. Furthermore, as different assessment tools resulted in having been used, in future research, greater attention should be paid to standardizing assessment tools and criteria for the autism spectrum, paying attention to the subjects presenting subthreshold traits as well. In general, future research should better investigate specific existential dimensions and/or difficulties met by people presenting both ASD and Gender Dysphoria.